2015
DOI: 10.1039/c5sc02052b
|View full text |Cite
|
Sign up to set email alerts
|

Tetraarylborate polymer networks as single-ion conducting solid electrolytes

Abstract: A new family of solid polymer electrolytes based upon anionic tetrakis(phenyl)borate tetrahedral nodes and linear bis-alkyne linkers is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
66
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(81 citation statements)
references
References 53 publications
10
66
0
5
Order By: Relevance
“…Similar microporous borate networks were investigated by Long et al Here too, lithium cations were introduced inside the anionic polymers post-synthetically and the structures were tested for lithium conductivity showing promising potential for an application as solid electrolytes in lithium ion batteries. 209 In an analogous approach Zhu et al reported the synthesis of anionic microporous borate based networks based on unfluorinated tetraphenylborate WCAs (Fig. 14).…”
Section: Anionic Microporous Polymersmentioning
confidence: 99%
“…Similar microporous borate networks were investigated by Long et al Here too, lithium cations were introduced inside the anionic polymers post-synthetically and the structures were tested for lithium conductivity showing promising potential for an application as solid electrolytes in lithium ion batteries. 209 In an analogous approach Zhu et al reported the synthesis of anionic microporous borate based networks based on unfluorinated tetraphenylborate WCAs (Fig. 14).…”
Section: Anionic Microporous Polymersmentioning
confidence: 99%
“…[10,11] In addition, given the ionic character,C OFs linked by spiroborates have the potential to function as ion conductive materials. [12][13][14][15][16][17] The spiroborate linkage can be formed readily through the condensation of polyols with alkali tetraborate, [11,[18][19][20] or boric acid, [21][22][23] or through the transesterification between borate and polyols [10] in athermodynamic manner.Previously, spiroborate linkages have been successfully used in the construction of macrocycles [10,22,[24][25] which show interesting applications as electrolytes, [26] sensors, [23,27] catalysts, [28] and hosts of neutral molecules or ions. [22,29,30] Although the spiroborate formation is reversible,s table,a nd easily accessible,t hus suitable for construction of COFs,i th as not yet been explored in the synthesis of COFs.H erein, we present the design and synthesis of porous spiroborate-linked ionic COFs (ICOFs) that exhibit excellent stability in water, high uptake of H 2 and CH 4 ,a nd also high room-temperature ion conductivity.…”
mentioning
confidence: 99%
“…Control over the distance between anionic species within electrolytes is predicted to be a critical factor in engendering efficient site‐to‐site cation hopping and ultimately high conductivity . In this regard, robust and tunable porous aromatic frameworks are promising candidates for porous electrolytes—indeed, interpenetration often places their functional groups in close proximity, which has been shown to enhance ion conduction and uptake as well as gas storage and separation properties .…”
mentioning
confidence: 99%
“…Control over the distance between anionic species within electrolytes is predicted to be a critical factor in engendering efficient site‐to‐site cation hopping and ultimately high conductivity . In this regard, robust and tunable porous aromatic frameworks are promising candidates for porous electrolytes—indeed, interpenetration often places their functional groups in close proximity, which has been shown to enhance ion conduction and uptake as well as gas storage and separation properties . Some of us previously reported ionic conductivities as high as 2.7 × 10 −4 S cm −1 for interpenetrated frameworks containing weakly coordinating borate anions, but the insolubility and infusibility of these materials limited post‐synthetic processing, hindering the incorporation into the battery cell.…”
mentioning
confidence: 99%